Analysis Of The Influence Of Diet On Dental Caries In 5th Graders At SD N 1 Genuksuran, Purwodadi District - Wahyu Dewi Hapsari; Meity Mulya Susanti; Yusri Nur'alimah (LPPM AN NUUR, 2021)
Background: Dental caries that often occurs among children. According to data from the Grobogan District Health Office in 2018, dental caries was ranked first with the highest incidence rate of 4,522 cases, and 1,062 cases of SD / MI. Often children like sweet foods and not maintaining their diet is suspected to be a factor in the cause of dental caries. Purpose: Knowing the effect of diet on dental caries in 5th grade children at public primary school 1 Genuksuran Purwodadi sub-district. Method: This was analytic survey research uses a case control research design with a retrospective approach. The sampling method used was purposive sampling technique where 38 respondents were divided into 2 groups, namely 19 respondents with dental caries and 19 the control groups had no dental caries. Results: Based on the analysis with the Chi-Square test found none thing that have an expected count value of < 5% and analysis betweendiet and dentel caries obtained p value 0,000 < 0,05. Conclusion: There is a significant influence between diet and dental caries in children grade 5 of SD N 1 Genuksuran Purwodadi sub-district